Raymond Schinazi Discusses the Discovery of Early Antiretroviral Agents and Sofosbuvir - Michael M. Lederman; Neil Greenspan (Case Western Reserve University, 2023)
In this interview, Raymond Schinazi, PhD, Hon DSc, talks about his career with Michael M. Lederman, MD, and Neil S. Greenspan, MD, PhD, senior editors of Pathogens and Immunity. Dr. Schinazi has invented numerous powerful antiviral agents including the antiretrovirals lamivudine (3TC) and emtricitabine (FTC) and was instrumental in the discovery of the anti-hepatitis C agent sofosbuvir. These drugs have saved millions of lives and, here, Dr. Schinazi shares in detail how these agents were invented, how they work, and how they are being applied. He also offers his thoughts about newer approaches to treat viral infections.